The Australasian Triage Scale Level 5 Criteria may Need to be Revised - Mirhaghi, Amir; Ebrahimi, Mohsen (Archives of Academic Emergency Medicine, 2017)
Australasian Triage Scale (ATS) is used to prioritize incoming patients in the emergency department (ED) according to patient acuity. It`s a five-level triage scale endorsed by the Australasian College for Emergency Medicine (ACEM). The ATS categories are defined by physiological predictors (airway, breathing, circulation, and disability) and maximum waiting time to treatment (1: immediate, 2: 10 minutes, 3: 30 minutes, 4: 60 minutes and 5: 120 minutes). Triage scales should be valid and reliable to ensure safe practice and promote clinical applicability in ED. Ebrahimi et al. reported that the pooled coefficient for ATS is fair: 0.390 (95% CI 0.307–0.466).